Influence of the β‐Sheet Content on the Mechanical Properties of Aggregates during Amyloid Fibrillization1. Issue 8 (14th January 2015) - Ruggeri, Francesco Simone; Adamcik, Jozef; Jeong, Jae Sun; Lashuel, Hilal A.; Mezzenga, Raffaele; Dietler, Giovanni
Abstract Amyloid fibrils associated with neurodegenerative diseases, such as Parkinson's and Alzheimer's, consist of insoluble aggregates of α‐synuclein and Aβ‐42 proteins with a high β‐sheet content. The aggregation of both proteins occurs by misfolding of the monomers and proceeds through the formation of intermediate oligomeric and protofibrillar species to give the final fibrillar cross‐β‐sheet structure. The morphological and mechanical properties of oligomers, protofibrils, and fibrils formed during the fibrillization process were investigated by thioflavin T fluorescence and circular dichroism in combination with AFM peak force quantitative nanomechanical technique. The results reveal an increase in the Young's modulus during the transformation from oligomers to mature fibrils, thus inferring that the difference in their mechanical properties is due to an internal structural change from a random coil to a structure with increased β‐sheet content.